THE REPRESENTATION OF SOCIAL JUSTICE IN CONTEMLORARY AMERICAN DRAMA - Maratova Farangiz Xasan qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Contemporary American drama is no longer a mere reflection of society; it has become a powerful instrument for social change, utilizing the stage as a platform to challenge injustice and champion equality. This essay explores how contemporary American plays engage with social justice issues, illuminating marginalized voices, tackling systemic inequalities, and provoking audiences to confront uncomfortable truths.